The sword thief - Lerangis, Peter (New York : Scholastic, 2009)
Amy and Dan Cahill travel to Japan to find the third clue.
"Read the books. Play the game. Win the prizes."--Cover.
Keywords: Family secrets -- Juvenile fiction; Code and cipher stories -- Juvenile fiction; Detective and mystery stories -- Juvenile fiction